Heat Transfer in Unitanks - Varma, Ravi R. (BrewingScience, 1999)
In the following article the author summarizes his work on heat transfer in Unitanks. The engineering aspects involved in sizing cooling areas for a Unitank are discussed and the different inputs to be specified by the brewer and the designer, essential to arrive at a satisfactory solution, are listed. The implications of varying the inputs on the final result are explained with illustrations in specific cases. Basic heat transfer equations, theories involved and a stepwise procedure to solve the problem are included. Results from a computer based programme developed for this application are tabulated and the utility of such a model for an optimum solution is explained.